Ecological indicators and bioindicator plant species for biomonitoring industrial pollution: Eco-based environmental assessment - Ines Terwayet Bayouli (Elsevier, 2021)
Industrial pollution remains a driving force to ecosystem alteration. Pollutants are released in the atmosphere interacting in turn with other components of earth system such as plant species. Despite the long-term exposition of vegetation cover to pollution is drastically devastating, less is known about the contribution of ecological indicators for its monitoring. The aims of this study are (i) to introduce the ecological indicators in assessing the cement dust impact on plant species and its biomonitoring and (ii) to screen new indicator species for phytoremediation studies. Floristic surveys were conducted in the cement plant closeness following quadrat method. Vegetation indicators such as total plant cover, perennial and annual species densities and diversity were assessed. Bioindicator species were identified using the bioaccumulation factor (BF) and translocation factor (TF). A decrease of perennial species richness and a decline of total vegetation cover by 7 times as well as a diversity decrease ranging from 2.99 to 2.31 were found pertinent indicators of land degradation in the industrial area. Annual species densities were significantly affected by cement pollution. Species like Lygeum spartum, Atractylis serratuloides and Gymnocarpos decander arise as indicators of heavy metals pollution. Pollution in the cement plant vicinity excluded sensitive species like Helianthemum kahiricum, Stipa tenassissima, Plantago coronopus. This study allowed the identification of indicator species of potential use in phytoremediation applications and emphasized the possibility of relaying on the vegetation indicators to assess the impact of cement pollution.